Benarkah Perempuan Paling Sering Membandingkan Diri di Lingkungan Sosialnya? - Amalia, Dini (Psikologi UHAMKA, 2025)
The ease of access in this digitalization era makes social media the main means of obtaining information about other people's lives. Without realizing it, such actions can provoke individuals to evaluate themselves by comparing themselves with others in the social media frame. The purpose of this study is to find out which gender groups most often make social comparisons in the context of social media. Respondents in this study totaled 170 people who were born in 1997 to 2012 (Generation Z), TikTok users, and live in the Jabodetabek area. In this study, respondents were divided into two groups, namely the experimental group (female group with code 1) and the control group (male group with code 0). The social comparison measuring instrument uses a social comparison scale which has two dimensions, namely opinion and ability (Gibbons & Buunk, 1999). Then, it was modified by Moningka & Ratih Eminiar (2020) into the context of social media with a measuring instrument reliability coefficient of 0.793. The linear regression analysis method is used to determine how much influence gender as an independent variable has on social comparison which is the dependent variable. Data analysis was carried out with the help of JASP software Ver. 0.19.3.0. Based on the analysis conducted, it is known that gender has a significant influence of 2.9% on social comparison, with an R2 value of 0.029. In addition, it can also be concluded that women compare themselves more often on social media than men (R = 0.169; B = 0.169; P = 0.027).